“Fear of stopping” vs “wanting to get off the medication”: exploring women’s experiences of using domperidone as a galactagogue - a qualitative study - Gabriella Zizzo; Alice R. Rumbold; Luke E. Grzeskowiak (International Breastfeeding Journal, 2021)
Abstract Background Domperidone is the most frequently prescribed medicine used to increase breast milk supply. There is considerable controversy surrounding the use of domperidone in lactation, due to limited evidence about efficacy and concerns about rare but life-threatening side-effects. Despite this, in many high-income settings such as Australia, use of domperidone among breastfeeding mothers appears to be increasing. The aim of this paper was to explore women’s experiences of using domperidone during breastfeeding. Methods Semi-structured interviews were conducted in 2019 with 15 women in Australia who reported using domperidone as a galactagogue during breastfeeding. Interviews were recorded, transcribed and analysed thematically. Results Women reported a wide variety of practices concerning the timing of initiation of domperidone use, including prophylactic use, as well as the dose and duration of use. Prolonged periods of use and unsupervised dosing were commonly reported, these practices were sometimes associated with a fear of the consequences of stopping, insufficient provision of information about the drug or feeling dismissed by health professionals. Some women indicated that when doctors refused to prescribe domperidone they responded by doctor shopping and seeking anecdotal information about benefits and risks online, leading to unsupervised practices. Women often reported high expectations surrounding the effectiveness of domperidone, and most used the medication in conjunction with food/herbal galactagogues and non-galactagogue support. Positive outcomes following domperidone use included having greater confidence in breastfeeding and pride at achieving breastfeeding goals. Conclusions This study identified a variety of practices concerning domperidone use, including potentially unsafe practices, linked in some cases to inconsistent advice from health professionals and a reliance on online, anecdotal information sources. These findings emphasise the urgent need for development of clinical practice guidelines and a greater focus on translating existing evidence concerning domperidone into clinical practice, including clinical support that is tailored to women’s needs.